2013
DOI: 10.1016/j.semcancer.2013.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and learning of molecular networks as a description of cancer development at the systems-level: Potential use in anti-cancer therapies

Abstract: There is a widening recognition that cancer cells are products of complex developmental processes. Carcinogenesis and metastasis formation are increasingly described as systems-level, network phenomena. Here we propose that malignant transformation is a two-phase process, where an initial increase of system plasticity is followed by a decrease of plasticity at late stages of carcinogenesis as a model of cellular learning. We describe the hallmarks of increased system plasticity of early, tumor initiating cells… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 101 publications
(147 reference statements)
0
22
0
Order By: Relevance
“…MMPs promote cell invasion and migration in several types of cancers, such as osteosarcoma, prostate, lung, colon and pancreas cancer (28). Compared with normal tissues, a higher expression of MMPs is often observed in malignant tumor tissues (29). Taken together, our study demonstrated that the ability of miR-142 to inhibit osteosarcoma cell invasion was achieved by inducing E-cadherin expression and reducing expression of MMP2 and MMP9.…”
Section: Discussionmentioning
confidence: 53%
“…MMPs promote cell invasion and migration in several types of cancers, such as osteosarcoma, prostate, lung, colon and pancreas cancer (28). Compared with normal tissues, a higher expression of MMPs is often observed in malignant tumor tissues (29). Taken together, our study demonstrated that the ability of miR-142 to inhibit osteosarcoma cell invasion was achieved by inducing E-cadherin expression and reducing expression of MMP2 and MMP9.…”
Section: Discussionmentioning
confidence: 53%
“…Kharchenko et al [136] discuss the genetic control of metabolism, but the temporal component comes from modeling, not measurement. Gyurkó et al [89] discuss the use of networks of individual proteins to understand the development of cancer. Taylor et al [292] argue that temporal reorganizations of the protein interaction network (the network of proteins that do interact, not the network of proteins that could interact) could predict and explain the development of breast cancer.…”
Section: Biological Networkmentioning
confidence: 99%
“…Human tumor development is a very complex process and the pathological process is high regulated by signal transduction [7]. PI3K/Akt/mTOR signaling, one of the three major signaling pathway that have been identified as important in cancer, is highly active in glioma and plays a pivotal role in cell survival, proliferation, and angiogenesis, and is frequently deregulated in human cancer [14].…”
Section: Introductionmentioning
confidence: 99%